Pelatihan dan Pendampingan Pembuatan QRIS pada Sentra Industri di Alat Dapur di Kota Semarang - Stacia Mege; Suwandi Suwandi; Nurul Imani Kurniawati (GOTAVA, 2023)
Rapid technological developments produce various kinds of innovations that aim to facilitate all human activities, including business activities. Business actors are provided with various kinds of conveniences through these technological advances, such as selling online so they don't build physical stores, expanding the target market by selling overseas, business bookkeeping that is made easier with various applications, to payment methods that are increasingly leading to cashless, and with QRIS, buyers can make payment transactions through mobile banking applications from various banks, electronic money, or electronic wallets which are increasingly prevalent in Indonesia. The obstacle faced was when the technology could not be utilized by most business actors. To overcome this problem, the service team conducted training for the kitchen appliance industry center in Semarang. The method chosen to overcome the problems that exist with partners is first the socialization of providing material to provide a detailed explanation of the topic. The second method is by training. This training method is very suitable for MSMEs so that they can directly practice the material that has been studied before. The results of this activity indicate that there is a need to modernize payment methods at all industry levels including at the small and medium business level, the use of QRIS will make sellers more helpful in terms of transactions.